Driving Forces Behind Depleting Forest Resources and Environmental Degradation in Northern Temperate of Pakistan - Sultan Muhammad; Moazzam Nizami; Muhammad Tayyab Khan; Nadim Arbab; Kaleem Mehmood; Hina Jabeen; Uzair Khan; Islam Zada; Muhammad Haseen Ullah; Brekhna Gul; et al. (Kurdish Studies, 2024)
Depleting forest resources in coniferous forests of northern temperate region in Khyber Pakhtunkhwa present severe ecological challenges. This research investigates the factors contributing to the decline of forests, employing both a pretested survey and detailed interviews with 100 residents. The study identifies rapid hotel construction driven by tourism and new access roads as the primary cause of forest depletion, with illegal timber activities, unauthorized grazing, local resource dependence, and poor management also contributing to the degradation. To mitigate these issues, the study advocates for the promotion of controlled, ecotourism-driven development, along with the regulation of road expansion.